1988
DOI: 10.1016/0735-1097(88)92605-8
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular distensibility and passive elastic stiffness in atrial septal defect

Abstract: Diminished left ventricular distensibility has been postulated as a cause of left ventricular failure in atrial septal defect. To evaluate this hypothesis the indexes of left ventricular compliance and stiffness were estimated in 15 patients with atrial septal defect and the results compared with those in 10 normal subjects. Age, peak left ventricular systolic pressure, end-diastolic pressure, ejection fraction and cardiac index did not differ significantly between groups. Left ventricular end-diastolic volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 26 publications
3
34
0
3
Order By: Relevance
“…This finding is consistent with that in humans with ASD (3,6). This result also explains the fact that the long-term growth of Tbx5 mutants is not affected, probably because the normal systemic cardiac output is maintained.…”
Section: Left Ventricular Diastolic Dysfunction In Tbx5 Del/ϩ Micesupporting
confidence: 81%
See 2 more Smart Citations
“…This finding is consistent with that in humans with ASD (3,6). This result also explains the fact that the long-term growth of Tbx5 mutants is not affected, probably because the normal systemic cardiac output is maintained.…”
Section: Left Ventricular Diastolic Dysfunction In Tbx5 Del/ϩ Micesupporting
confidence: 81%
“…In humans with ASD, right ventricular dilatation significantly alters left ventricular geometry (e.g., a flattened inter- ventricular septum toward the left ventricle at end systole and early diastole and decreased left ventricular chamber dimension), increases left ventricular chamber stiffness and reduces its compliance, and consequently impairs left ventricular filling (3,6,17). However, all these abnormalities are not associated with significant changes in the mitral flow pattern in patients with normal pulmonary pressure (21,30,34).…”
Section: Possible Mechanisms For Left Ventricular Diastolic Dysfunctionmentioning
confidence: 89%
See 1 more Smart Citation
“…10 With similarly sized ASDs, therefore, adults tend to have larger shunts as they age. It is part of the reason why children are rarely symptomatic but patients in their fourth or fifth decade may begin to develop the symptoms frequently associated with ASD.…”
Section: Natural Historymentioning
confidence: 99%
“…Diastolic dysfunction of the left ventricle in the setting of atrial septal defect has been previously reported [5] and may be a consequence of diastolic ventricular interaction with constraint of left ventricular filling caused by right ventricular dilation [6]. This phenomenon is usually not clinically relevant in younger patients undergoing ASD closure as elasticity of the left ventricle can accommodate the extra preload following closure.…”
Section: Discussionmentioning
confidence: 96%